Narrow-diameter implants with conical connection for restoring the posterior edentulous region - Woo, In-Hee (Maxillofac Plast Reconstr Surg, 2016)
BACKGROUND: The objective of this retrospective study was to show results from platform-switched narrow-diameter implants in the posterior edentulous region, which we followed up for more than 1 year after functional loading. METHODS: Ninety-eight narrow implants were inserted into 66 patients. After healing, fixed implant-supported prostheses were delivered to the patients, and Periotest and radiographic examinations were performed. After the first year of loading, the implant outcome was again evaluated clinically and radiographically using the Periotest analysis. Crestal bone loss and Periotest values (PTVs) were used to evaluate the effect of surgery, prosthesis, implant, and a host-related factor. A general linear model was used to statistically detect variables statistically associated with crestal bone loss and Periotest value. RESULTS: We followed up on the implants over 1 to 4 years after loading; their survival rate was 100 %, and pronounced differences from PTVs were noted among jaw location, bone quality, and loading period. No difference was detected in bone loss among the variables studied. Bone loss after functional loading was 0.14 ± 0.39 mm. The stability value from the Periotest was −3.29 ± 0.50. CONCLUSIONS: Within the limitations of this study, judicious use of platform-switched narrow implants with a conical connection must be considered an alternative for wide-diameter implants to restore a posterior edentulous region.